TREE COMMUNITY COMPOSITION AND STRUCTURE OF CACAO (THEOBROMA CACAO L.) BASED AGROFORESTRY IN WEST SUMATERA, INDONESIA - Santhyami, Santhyami; Basukriadi, Adi; Abdulhadi, Rochadi (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
The aim of this study is to obtain basic descriptive account of structure and floristic composition of cacao based agroforestry in conserving tree species diversity in West Sumatera. An analysis of the composition and structure of three types of cacao based agroforestry system (AFS) [cacao - rubber (CR), cacao ? coconut (CC) and cacao multistrata (CM)] was conducted in April to June 2017. Data collection was done by using quadrat method of 20 x 20 meter plots with a total of 6 plots on each types of AFS. Herbarium specimens were collected and identified. Among all types of these AFS, CC was the most diverse floristically (H? = 1.02) with the highest total of species (10 species), followed by CM (9 species) and CR (7 species). CM has the highest tree density of 1108 trees per ha and the highest total of basal area (30.53 m2). We also did a comparison of the floristic composition of cacao based AFS with the nearest natural forest from previous study. There was a large decrease in the number of non-cocoa tree species from natural forest to AFS, from 139 to 6-9 species. The only native tree species found both in the forest and AFS is Pterospermum javanicum Jungh. It is concluded that three types of cocoa based AFS in West Sumatera were floristically different with natural forest.